The importance of relationship processes for lowering BMI over time in women with type 2 diabetes in a randomized controlled trial. Issue 6 (November 2019) - Yorgason, Jeremy B.; Sandberg, Jonathan G.; Weinstock, Ruth S.; Trief, Paula M.; Fisher, Lawrence; Hessler, Danielle
Abstract: Objective: Weight change may be affected by dyadic processes within couple relationships. The aim of this secondary data analysis was to explore trends in BMI across time, and assess whether relationship processes (i.e., relationship satisfaction, positive problem-solving), predict BMI trajectories in men and women. Methods: Data are from 268 participants in the Diabetes Support Project, a randomized trial of behavioral intervention for individuals with type 2 diabetes (T2D) in poor glycemic control. For secondary analyses, BMI was measured at pre-treatment (baseline), 4 months (post-treatment), 8 months, and 12 months. Multiple relationship variables were measured at all time points and were modeled as predictors and correlates of change in BMI across time. Results: In general, BMI trajectories had higher starting values (intercepts) for females than for males in the sample (b = −2.51, p < .05), and slopes trended downward from pre-treatment to 12 months (b = −.09, p < .05). Downward trajectories of BMI were more pronounced for women with higher relationship satisfaction (b = .05, p < .05) and higher positive problem solving skills (b = .06, p < .05) at baseline. Change in relationship processes were not correlated with change in BMI across time. Conclusion: For women with T2D in this behavioral intervention study, relationship process scores at the beginning of treatment predicted changes in BMI over time, with better problem solving and higher relationship satisfaction at baseline related to steeper decreases in BMI across treatment. Additional research is needed to understand how improving relationship interaction prior to diabetes treatment may positively influence weight loss during treatment.